2015
DOI: 10.1371/journal.pone.0137098
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of EcbHLH57 Transcription Factor from Eleusine coracana L. in Tobacco Confers Tolerance to Salt, Oxidative and Drought Stress

Abstract: Basic helix-loop-helix (bHLH) transcription factors constitute one of the largest families in plants and are known to be involved in various developmental processes and stress tolerance. We report the characterization of a stress responsive bHLH transcription factor from stress adapted species finger millet which is homologous to OsbHLH57 and designated as EcbHLH57. The full length sequence of EcbHLH57 consisted of 256 amino acids with a conserved bHLH domain followed by leucine repeats. In finger millet, EcbH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 76 publications
0
58
0
Order By: Relevance
“…Quantitative PCR (qPCR) was carried out to evaluate the transcript accumulation of SlTCTP (using the qTCTP primer pair) and selected stress-responsive genes (NtLEA14, NtRD29A and NtERD1; primers according to Babitha et al 2015) in the generated transgenic tobacco lines, and also to check the accuracy of the generated RNA-Seq data employing a set of 17 selected genes (for details see Table S1). In the last case, the same RNA samples used for RNA-Seq library construction were employed.…”
Section: Qpcr Assaysmentioning
confidence: 99%
“…Quantitative PCR (qPCR) was carried out to evaluate the transcript accumulation of SlTCTP (using the qTCTP primer pair) and selected stress-responsive genes (NtLEA14, NtRD29A and NtERD1; primers according to Babitha et al 2015) in the generated transgenic tobacco lines, and also to check the accuracy of the generated RNA-Seq data employing a set of 17 selected genes (for details see Table S1). In the last case, the same RNA samples used for RNA-Seq library construction were employed.…”
Section: Qpcr Assaysmentioning
confidence: 99%
“…The CsbHLH18 of sweet orange functions in the modulation of cold tolerance by regulating the antioxidant gene [49]. Some bHLH transcription factors can also respond to salinity and Fe-deficient abiotic stress [50,51]. In the present study, the biological process of GO annotation showed that most of genes had the GO terms of cellular N compound, metabolic process, biosynthetic process, anatomical structure development, response to stress, regulation of transcription, DNA template, and reproduction.…”
Section: Go Annotation Of Bolbhlh Genes Indicated Their Functionsmentioning
confidence: 49%
“…In recent years, many studies have shown that TFs are essential in mediating salt stress response. For example, overexpression of NAC [ 39 ], MYB [ 40 ], heat shock transcription factor ( HSF ) [ 41 ], WRKY [ 42 ], and bHLH [ 43 ] transcription factors can significantly improve salt tolerance in plants. In this study, 39 genes homologous to NAC , MYB , HSF , WRKY , bHLH , ERF , homeo-box ( HB ), and other TFs , were significantly up-regulated by salt treatment ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%